Answer:
1440 ft squared
Step-by-step explanation:
v = lwh (length times with time height)
Hope this helps Buddy!
- Courtney
Answer:
<h2>C. G(x) = (x - 1)² - 3</h2>
Step-by-step explanation:
f(x) + n - shift the graph of f(x) n units up
f(x) - n - shift the graph of f(x) n units down
f(x - n) - shift the graph of f(x) n units to the right
f(x + n) - shift the graph of f(x) n units to the left
===================================
Look at the picture.
The graph of F(x) shifted 1 unit to the right and 3 units down.
Therefore the equation of the function G(x) is
![G(x)=(x-1)^2-3](https://tex.z-dn.net/?f=G%28x%29%3D%28x-1%29%5E2-3)
Answer:
well I mean I already am gay well I'm really lesbian so take that!
He won about 25% because 6/12 would be 1/2 and 3 is 1/2 of 6 or a 1/4 so 25%